KUALITAS TIDUR YANG BURUK AKIBAT GANGGUAN MAKAN PADA PELAJAR SEKOLAH MENENGAH DI JAKARTA - Markus Julian; Felicia Kurniawan (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Eating disorders can affect sleep quality, especially teenagers, because adolescence is a period of physical and psychological changes. Hormone release and glucose metabolism occur during sleep, whereas the neuroendocrine system influences appetite. This study objective is to find out the association of the risk of eating disorders with adolescents sleep quality because adolescents today have not cared about eating time and food consumed. Methods: This research was cross-sectional analytic research of 275 respondents of junior and senior high school students in an international school located in West Jakarta who met the inclusion criteria in October 2019. The measuring instrument was a demographic questionnaire, screening questionnaire, Eating disorder Examination Questionnaire (EDE-Q) and Pittsburgh Sleep Quality Index (PSQI). Bivariate analysis was used to analyze the correlation between the risk of eating disorder and sleep quality.Results: Most respondents were women as many as 173 people (62,9%), while men as many as 102 people (37,1%). Most respondents, 125 people (45,5%), were 12-13 years old, and the class with most respondents was class 8 as many as 62 people (22,6%). Respondents with the risk of eating disorders as many as 156 people (56,7%) while those with poor sleep quality as many as 240 people (87,3%). Among respondents with the risk of eating disorders, 151 people (96,8%) had poor sleep quality, and five people (3.,2%) had good sleep quality. Chi-square test results showed a significant relationship between the risk of eating disorder with sleep quality (p=0,000) Conclusion: There is a relationship between the risk of eating disorders on sleep quality in junior and senior school students at Kairos Gracia International School in 2019, so the students need to be given knowledge and advice as well counselling for the student who has a risk of eating disorder to achieve a better quality of life